A Study Review on Spinel as Interconnect Coating for Solid Oxide Fuel Cell (SOFC) - Mohd Hisham, Muammar Syamim Hamizan; Azmi, Mohd Azham (Research Progress in Mechanical and Manufacturing Engineering, 2022)
A solid oxide fuel cell (SOFC) is a green and reliable alternative energy source that under development which generates electricity. In order to understand the spinel as interconnect coating of Solid Oxide Fuel Cell (SOFC), a review has been conducted. The review was about understanding on how Mn-Co spinel coating that has been successfully fabricated, so that the technique of Electrophoretic Deposition (EPD) was used to produce the desired coating effectively. The (Mn,Co)3O4 spinel coatings on the surface of Cr-containing steel through electrophoretic deposition (EPD) are followed by reduced-atmosphere sintering for solid oxide fuel cell (SOFC) interconnect application. The review was about the effects of EPD voltages and sintering atmospheres on the microstructure, electrical conductivity and long-term stability of the coated interconnects are examined by means of scanning electron microscopy (SEM), energy dispersion spectrometry (EDS) and Electro Impedance Spectroscopy (EIS). SOFC performance with different voltages and coating durations parameter are analysed. Therefore, the EPD technique has successfully provided that better coating thickness of spinel as interconnect for SOFC.